Dataset: human mobility messages on Telegram - Tucci, Giulia; Silveira Carneiro, Bia; Ruscica, Giosue Stefano; Riccio, Benedetta; Lundgaard, Daniel; Ippolito, Heidi; de Andrade Silva, Sara; Aboofazeli, Tahereh; Freschi, Ricardo; Livad, Aliki (2024)
This dataset comprises six sets of IDs of messages about human mobility shared on thematic Telegram public groups and channels. Messages were queried using TeleCatch, an Open Scource tool that enables visualizing, filtering, and extracting Telegram messages data and image files. This dataset was created during the 2024 Digital Methods Initiative Summer School for the project "Uncovering visual narratives about human mobility on Telegram".